Therapeutic potential of Chinese herbal medicine for coronary heart disease patients with cerebral ischemic stroke: a systematic review and meta-analysis - Du, Rui; Ao, Yuhan; Wang, Yang; Chen, Zhihui; Liu, Guanghui; Zhang, Mingxue (Frontiers in Pharmacology, 2025)
ObjectiveThis research sought to demonstrate potential therapeutic strategies for coronary heart disease (CHD) patients with cerebral ischemic stroke (CIS) by rigorously evaluating the efficacy and safety of Chinese Herbal Medicine (CHM) through meta-analysis.MethodsA broad search approach was applied to obtain pertinent articles from both domestic and international databases, covering publications up to 31 December 2024. Using RevMan software (Version 5.4), a systematic review and meta-analysis were conducted to assess the efficacy and safety of CHM in treating CHD patients with CIS.ResultsIn the meta-analysis, 18 trails were analyzed, encompassing 2,202 patients in total. The aggregated findings indicated that the utilization of CHM improved the overall effective rate, ECG performance and TCM scores significantly. Furthermore, the CHM therapy demonstrated significant improvements in LVEF, MMSE, and NIHSS. Additionally, the CHMs therapy positively influenced lipid profiles, specifically TC, TG, LDL-C, and HDL-C. Notably, the application of CHM during the intervention was particularly effective in reducing blood viscosity, fibrinogen and platelet aggregation. Importantly, the CHM therapy was found to provide comparable safety profile to that of conventional western medicine treatment (WM) alone.ConclusionThe CHM demonstrated superior efficacy in the management of CHD patients with CIS. Concurrently, the CHM showed potential for improving neurological damage, lipid profiles, and positively affecting hemorheological parameters, all while minimizing the risk of adverse effects. Even so, because of the limitations in study quality and the potential for reporting bias, it is crucial that these findings require to be further validated through rigorous, large-scale, and high-quality RCT in future research.